PENGUKURAN KUALITAS KECEPATAN ANGIN PADA TEROWONGAN ANGIN DI ILST BBTA3 - Risnawan, Novan; Yohanes, F. Andree; Sunarno, Sunarno; Novianti, Hetty; Feriadi, Yusron (-)
AbstractCalibration check of Indonesia Low Speed Wind Tunnel (ILST) flow reference value have been performed at the beginning of 2018. Calibration check have been conducted to the calibration coefficient of predicted freestream static and dynamic pressure. This wind tunnel reference values is reffered to the static and dynamic pressure of a reference pitot tube that is installed at the center of turn table inside the test section. The test is conducted in empty test section. The calibration check result is very close to the previous values. This result show that flow quality of ILST wind tunnel is still maintained well for aerodynamic testing purposes.Keywords: Wind tunnel calibration, tunnel reference value. AbstrakPengecekan hasil kalibrasi besaran-besaran acuan aliran terowongan angin ILST telah selesai dilakukan pada awal tahun 2018. Pengecekan kalibrasi dilakukan terhadap koefisien kalibrasi tekanan statik dan tekanan dinamik terprediksi. Koefisien-koefisien referensi terowongan angin ini disesuaikan dengan tekanan statik dan tekanan dinamik yang dibaca oleh pitot tube acuan yang dipasang di tengah turn table di dalam seksi uji. Pengukuran dilakukan pada kondisi seksi uji kosong (empty test section). Hasil pengecekan kalibrasi acuan ini sangat dekat dengan hasil sebelumnya. Hasil kegiatan ini secara umum menunjukkan bahwa kualitas aliran terowongan angin ILST masih terpelihara dengan baik untuk keperluan pengujian aerodinamik.Kata Kunci : Kalibrasi terowongan angin, referensi terowongan angin.